Theoretical and comparative study regarding the Galerkin-Vlasov method use for study the free vibrations of wood flat plate - Fetea, Marius; Cheregi, Gabriel; Lustun, Liana; Smit, Ildico; Lucaci, Codruta; Galis, Ioan; Dubau, Calin; Derecichei, Laura; Sotoc, Horea; Burescu, Laviniu; Teodora, Codau (Acta Agraria Debreceniensis, 2010)
As for the historic record of the problem related to the study of flat plates, the first results were out for publishing at the end of the 18th century, the beginning of the 19th century, having Chladni E, Strehlke, Konig, R, Tanaka S, Rayleigh L, Ritz W and later on Gontkevich V, Timoshenko S, Leissa as pioneers. Each of the above mentioned authors have had significant contributions regarding the development of methods in order to solve the plates and establish some rigurous solutions of their differential equations of equilibrium. The making of constructions, machines and different high-perfomance appliances, whose functioning should take place in safety conditions, have required theoretical studies of rich complexity, as well as practical experiments, within which the problem of their free and forced vibrations represent an important category in the respective theme of research.